2014
DOI: 10.1177/1687814020974909
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies on the influence of inlet guide vanes of centrifugal compressor on the flow field characteristics of inlet chamber

Abstract: Inlet chambers (IC) are the typical upstream component of centrifugal compressors, and inlet guide vanes in the IC have a great impact on its internal flow and aerodynamic loss, which will significantly influence the performance of the downstream compressor stages. In this paper, an experimental study was carried out on the flow characteristics inside a radial IC of an industrial centrifugal compressor, including five testing sections and 968 measuring points for two schemes with and without guide vanes. Detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition, the qualities of the computational grids are provided in Table 3, proving that good grid quality was achieved for the present numerical solutions. In order to validate the reliability of the numerical results in the present study, the calculated flow parameters on the main sections in the radial inlet chamber and the predicted performance of the compressor stage were extracted and compared against the experimental results of the previously published literature [36,37].…”
Section: Grid Convergence Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the qualities of the computational grids are provided in Table 3, proving that good grid quality was achieved for the present numerical solutions. In order to validate the reliability of the numerical results in the present study, the calculated flow parameters on the main sections in the radial inlet chamber and the predicted performance of the compressor stage were extracted and compared against the experimental results of the previously published literature [36,37].…”
Section: Grid Convergence Studymentioning
confidence: 99%
“…For the flow analysis of the inlet chamber itself, the computational model included a radial inlet chamber (with or without guide vanes), a straight inlet pipe and an outlet pipe, as shown in Figure 2a. All the patches were modeled with data from the previous experimental research [36,37]. Meanwhile, as shown in Figure 2b, a computational model of the radial inlet compressor stage was built for the study on the performance improvement and downstream effects of the radial inlet chamber.…”
Section: Computational Modelsmentioning
confidence: 99%
“…The influence of the change of the flow field in the separator and the separation effect. [14][15][16][17][18][19][20] In this paper, the CFX software is used to establish the simulation model of the separator of each structure. Through the simulation comparison, a new type of separator with a structure is selected.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng and Ding 26 studied the effect of temperature and pressure on the stress of impeller in centrifugal compressor, and found that temperature effect is large for low inlet temperature, reaching 57% of the total equivalent stress, and the temperature mainly affects the stress on the hub and the root of the blade, and the pressure mainly influences the stress on the blade part. Han et al 27 investigated the influence of inlet guide vanes of centrifugal compressor on the flow field characteristics of inlet chamber (IC), and numerical simulations were performed to further analyze the flow characteristic inside the radial IC. Pan et al 28 studied the prefabricated crack propagation of FV520B specimen with unilateral gap by numerical simulation, and the results show that the maximum value of stressstrain located at the tip of the crack, and the crack propagation path is perpendicular to the load loading direction.…”
Section: Introductionmentioning
confidence: 99%